Anthropometrical and Nutritional Associations with Intraoperatively Dexamethasone and Tranexamic Acid in Risk Propensity for Post -Rhinoplastic Subconjunctival Hemorrhages - MOHAMMAD AL KATATBEH; MD, YAZAN AL-MASHAKBEH; MD (South Eastern European Journal of Public Health, 2025)
Objectives: The study aimed to assess the correlation between potential confounders and factors like tranexamic acid use, multivitamin supplementation, dexamethasone administration, postrhinoplasty thermoplastic splinting, and patients' demographic and obesity statuses on the likelihood of achieving or maintaining a certain grade according to the subconjunctival hemorrhages (SCH) grading system, and to assess recovery within one-week post-procedure. Methods: Hashemite University in Zarqa, Jordan, conducted a 2019–2023 retrospective study of rhino plastically treated patients. Prior surgery, cardiovascular or coagulopathy disorders, uncontrolled blood pressure, and adults under 18 or over 60 were excluded from the study. Patients were instructed to schedule procedures according to their menstrual cycle and use non-compressive nasal packing. Patients received antibiotics and analgesics post-operative. Kara et al.'s grading system was used to assess post-rhinoplastic procedural subconjunctival haemorrhages on the first and second days after the procedure. The study also examined the effects of cerebral haemorrhage severity, recovery likelihood, and residual clinical significance over one week. The study employed both chi-square and multiple logistic regression tests in its statistical analyses to derive the corresponding p-values. Results: A study involving 269 patients underwent rhinoplasty surgery, with 53.16% female and 46.84% male. The study found that two significant factors were the perioperative administration of 2 g infusion of tranexamic acid and the preoperative supplementation of multivitamins with or without trace elements. The estimated risk for tranexamic infusion was 0.022, and for multivitamins supplementation it was 0.316. The logistic regression model was developed to incorporate the probability of subconjunctival hemorrhages 1st day with prediction variability ranging from 44.2% to 59.0%. The likelihood in the 2nd was found to be statistically significant with only preoperative multivitamins supplementation, preoperative dexamethasone provision, and obesity statuses of the patients. Conclusion: The study suggests that tranexamic acid can reduce grade 2 subconjunctival haemorrhages on the first day after rhinoplastic surgery, while obesity increases the risk. Dexamethasone can reduce moderate bleeding and accelerate recovery. Consistent multivitamin use, lowering body mass index, and using tranexamic acid during surgery are recommended